CONTRIBUTIONS OF SOME NIGERIAN ARTISTS IN TERTIARY INSTITUTIONAL ADMINISTRATION - Kaliku, Razq Olatunde Rom; Odeniyi, Akinkunmi Olatunbosun (Srawung: Journal of Social Sciences and Humanities, 2024)
The emergence of modern Nigerian art was premised on the efforts of artists. In the study of Nigerian artists, early-generation artists were the focus. The studies were not particularly concentrated on artists in Nigerian Art schools. Whereas, after the initial studies, more artists have evolved with enormous contributions. Later-generation artists, particularly those with significant contributions to Nigerian Art school development deserve adequate scholastic attention. There is consequently a dearth of scholarship on later-generation artists in Nigerian Art schools. This study aims to provide information on the contributions of selected artists in Nigerian Art schools. The study biographically examined eleven selected Nigerian artists who, as pioneers, function in professional, academic, and administrative capacities in visual art departments in Nigerian universities. Findings revealed these artists’ contributions via the responsibilities they undertook as heads of the department, deans of faculty, vice-chancellors, visiting, associate or adjunct lecturers, external examiners, academic assessors, resource persons in programme audit and accreditation exercise, and consultants on the establishment of visual art departments. They are actively involved in the curriculum and developmental plan designing, teaching, research, and research supervision. They pilot the affairs of their departments by providing leadership at various points in time. Conclusively, their contributions are vital to the founding, growth, and sustenance of visual arts departments in Nigerian universities and Nigerian visual arts.